2020
DOI: 10.7181/acfs.2020.00325
|View full text |Cite
|
Sign up to set email alerts
|

Fat grafts enriched with adipose-derived stem cells

Abstract: Autologous fat grafts have been widely used in soft-tissue augmentation and reconstruction surgery. Despite their numerous advantages, including a simple harvest technique, low cost, and easy accessibility, the applicability of autologous fat grafts is limited by their unpredictable long-term outcomes associated with poor graft retention [1,2]. In recent decades, several advances have been made to overcome the low rate of graft survival, including various refinements of existing techniques, the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…It is also thought to help keep the screws and nylon sling in its original position by weakening the muscle. Liposuction and autologous fat grafting have also been widely used in reconstruction and soft tissue augmentation, and recent research with the addition of adipose-derived stem cells are showing greater results [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also thought to help keep the screws and nylon sling in its original position by weakening the muscle. Liposuction and autologous fat grafting have also been widely used in reconstruction and soft tissue augmentation, and recent research with the addition of adipose-derived stem cells are showing greater results [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…These strategies may include the application of pharmacological compounds, such as angiogenic growth factors [ 39 ]. It may also be promising to combine fat grafting with cellular tissue engineering concepts for vascularization, including the co-transplantation with adipose tissue-derived stem cell-rich stromal vascular fraction [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…As fat grafting has become more popular, complications have also grown more common. Harvesting autologous fat using liposuction is a comfortable, repeatable, and low-cost procedure for most patients [ 11 , 12 ]. In 2009, a task force formed by the American Society of Plastic Surgeons assessed autologous fatgrafting techniques to determine their safety and efficacy [ 13 ] and reported that fat grafting is safe for various medical conditions, with a lower risk of com-plications than the risk levels recorded for other types of surgery.…”
Section: Discussionmentioning
confidence: 99%